Novel hydoxyapatite (HAp) nanoparticles production by supercritical carbon dioxide processing for drug delivery application (potential for various cancer treatments) - Midhat Nabil, Ahmad Salimi, Engr. Dr. (Universiti Malaysia Perlis (UniMAP), 2014)
Received a Gold medal in 25th International Invention, Innovation & Technology Exhibition (ITEX'14), 8th-10th May at Kuala Lumpur Convention Centre.